The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000007983
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a curved forceps with a conventional straight forceps for nasogastric tube insertion under videolaryngoscopic guidance

Abstract: Background:Nasogastric tube (NGT) insertion is an easy procedure that can be routinely performed under general anesthesia. However, for difficult cases, there are limited insertion techniques available in routine clinical practice, considering the flexibility of NGTs. The SUZY curved forceps are designed for the removal of pharyngolaryngeal foreign bodies under guidance of the McGRATH MAC (McG) videolaryngoscope. Because McG enables clear visualization of the esophageal inlet, we hypothesized that the SUZY for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Because NGT insertion was performed by skilled anesthesiologists in this study, the results cannot be simply applied to anesthesia trainees or residents. However, in our previous manikin study, [ 19 ] we showed that the skill required to insert an NGT using Magill forceps would be greater than when using SUZY forceps under McGrath videolaryngoscopic guidance. Therefore, if trainees or residents were to insert the NGT using either of these forceps, the difference may be larger than that found in our present study.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Because NGT insertion was performed by skilled anesthesiologists in this study, the results cannot be simply applied to anesthesia trainees or residents. However, in our previous manikin study, [ 19 ] we showed that the skill required to insert an NGT using Magill forceps would be greater than when using SUZY forceps under McGrath videolaryngoscopic guidance. Therefore, if trainees or residents were to insert the NGT using either of these forceps, the difference may be larger than that found in our present study.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous manikin study [ 19 ] demonstrated that SUZY forceps could advance the NGT for a longer distance than Magill forceps during insertion of the NGT from the pharynx to the esophagus. This advantage likely reduced the insertion time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations